The Pathological Phenotypes of Human TDP-43 Transgenic Mouse Models Are Independent of Downregulation of Mouse Tdp-43 - Xu, Ya-Fei (Public Library of Science, 2013)
Tar DNA binding protein 43 (TDP-43) is the major component of pathological deposits in frontotemporal lobar degeneration with TDP-43 inclusions (FTLD-TDP) and in amyotrophic lateral sclerosis (ALS). It has been reported that TDP-43 transgenic mouse models expressing human TDP-43 wild-type or ALS-associated mutations recapitulate certain ALS and FTLD pathological phenotypes. Of note, expression of human TDP-43 (hTDP-43) reduces the levels of mouse Tdp-43 (mTdp-43). However, it remained unclear whether the mechanisms through which TDP-43 induces ALS or FTLD-like pathologies resulted from a reduction in mTdp-43, an increase in hTDP-43, or a combination of both. In elucidating the role of mTdp-43 and hTDP-43 in hTDP-43 transgenic mice, we observed that reduction of mTdp-43 in non-transgenic mice by intraventricular brain injection of AAV1-shTardbp leads to a dramatic increase in the levels of splicing variants of mouse sortilin 1 and translin. However, the levels of these two abnormal splicing variants are not increased in hTDP-43 transgenic mice despite significant downregulation of mTdp-43 in these mice. Moreover, further downregulation of mTdp-43 in hTDP-43 hemizygous mice, which are asymptomatic, to the levels equivalent to that of mTdp-43 in hTDP-43 homozygous mice does not induce the pathological phenotypes observed in the homozygous mice. Lastly, the number of dendritic spines and the RNA levels of TDP-43 RNA targets critical for synapse formation and function are significantly decreased in symptomatic homozygous mice. Together, our findings indicate that mTdp-43 downregulation does not lead to a loss of function mechanism or account for the pathological phenotypes observed in hTDP-43 homozygous mice because hTDP-43 compensates for the reduction, and associated functions of mTdp-43. Rather, expression of hTDP-43 beyond a certain threshold leads to abnormal metabolism of TDP-43 RNA targets critical for neuronal structure and function, which might be responsible for the ALS or FTLD-like pathologies observed in homozygous hTDP-43 transgenic mice.